If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-84=-3(-4n+8)
We move all terms to the left:
-84-(-3(-4n+8))=0
We calculate terms in parentheses: -(-3(-4n+8)), so:We get rid of parentheses
-3(-4n+8)
We multiply parentheses
12n-24
Back to the equation:
-(12n-24)
-12n+24-84=0
We add all the numbers together, and all the variables
-12n-60=0
We move all terms containing n to the left, all other terms to the right
-12n=60
n=60/-12
n=-5
| -4=x/35+6 | | 37.2+x/6=7.5 | | 369.44=230+0.56x | | 4n-18=52n= | | 2(6-11)=y-9 | | 2y+31=y+7 | | 3z+7=21 | | 4p+10p-14=20 | | -4(4+2m)=-14-8m | | 24.95+.10=19.95+.20x | | x-2/3x+1=x+2/x | | x=(3/4)^5/(3/4)^3 | | 4g+5=21 | | 2/3y+y=31 | | y-31=6 | | 3x×18=x+12 | | .12(y-4)+0.06y=0.20y-0.6 | | -2.4g+1.2=1.2g+4.8 | | 7+6(w+3)=31 | | 20n=-375 | | 11x-4x+112=11x+72 | | -4w-1=2w+8 | | 3x-(x-1)=4x+7 | | 2y+3y=y+7 | | -4x+7=6x+3 | | 2x+4=-(-7x+x) | | -4b-2+5b=3b-4 | | 6t-1=-3t-1 | | 2x-5(x-5)=-9+2x+4 | | 7+5r=6r | | c-6=5c+10 | | -0.7x-15=-3.8 |